2002
DOI: 10.1046/j.1095-8339.2002.00072.x
|View full text |Cite
|
Sign up to set email alerts
|

Microsporogenesis, microgametogenesis and pollen morphology of Passiflora spp. (Passifloraceae)

Abstract: Microsporogenesis, microgametogenesis and pollen morphology of six species of genus Passiflora L. belonging to three subgenera (Passiflora, Dysosmia, Decaloba) were studied with light and scanning microscopy; P. caerulea was also examined with transmission microscopy. The tapetum is secretory, microspore tetrads are tetrahedral and pollen grains are two‐celled when shed. Small Ubisch bodies are attached to a peritapetal membrane; they are a product of tapetal activity and the rough endoplasmic reticulum (ERr) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
9

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 25 publications
(28 reference statements)
1
8
0
9
Order By: Relevance
“…Passiflora misera was considered by Araújo & Santos (2004) as having 6-colpi; it was 6-colpori, according to Presting (1965), Dettke & Santos (2009) and Evaldt et al (2011); 12 colpi, according to García et al (2002);and 12-colpori, according to Milward-de-Azevedo et al (2004;2010). The current study corroborates the results found by the last authors.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Passiflora misera was considered by Araújo & Santos (2004) as having 6-colpi; it was 6-colpori, according to Presting (1965), Dettke & Santos (2009) and Evaldt et al (2011); 12 colpi, according to García et al (2002);and 12-colpori, according to Milward-de-Azevedo et al (2004;2010). The current study corroborates the results found by the last authors.…”
Section: Discussionsupporting
confidence: 83%
“…Spirlet (1965) used pollen data to help taxonomic classification. Later studies such as those by García et al (2002), Araújo & Santos (2004), Milward-de-Azevedo et al (20042010), Barrios et al (2005), Dettke & Santos (2009), Evaldt et al (2011), Tangarife et al (2011), Mezzonato-Pires (2013 and Verdasca et al (2013) also helped improving the palynological knowledge on the Passifloraceae s.s. family.…”
mentioning
confidence: 99%
“…Os resultados obtidos no presente trabalho foram semelhantes aos encontrados por MacDougal (1994) no que se refere ao tamanho dos grãos de pólen, às características do retículo, lúmen e da exina, porém difere na quantidade de cólporos e na forma encontrada para P. morifolia que foi descrita, no presente estudo, como prolato-esferoidal e subprolata no material de comparação. García et al (2002), analisando a ontogenia e a palinologia de seis espécies de Passiflora pertencentes a três subgêneros -Passiflora, Dysosmia e Decaloba, estudaram os grãos de pólen de P. misera e P. suberosa. Segundo os autores, as medidas polínicas (n = 10) foram realizadas em microscópio de luz, com grãos de pólen não acetolisados, montados apenas em água glicerinada, pois o material submetido à acetólise variou consideravelmente na forma.…”
Section: Discussionunclassified
“…Presting (1965) realiza o estudo até então mais abrangente e pormenorizado sobre os grãos de pólen de Passifl oraceae, contemplando 153 espécies da família, distribuídas em 13 gêneros, destacando a importância do entendimento da evolução das aberturas dos grãos de pólen de Passifl oraceae para a realização das descrições polínicas. García et al (2002), no estudo da microesporogênese, microgametogênese e morfologia polínica de seis espécies de Passifl ora da Argentina; Araújo & Santos (2004), com o estudo morfológico de 12 espécies de Passifl ora da Bahia, estabelecendo três tipos polínicos entre as espécies estudadas; Milwardde-Azevedo et al (2004), com a descrição polínica de oito espécies de Passifl ora, subgênero Decaloba; e Barrios et al (2005), com a caracterização de 121 espécies de Passifl ora e duas espécies de Dilkea Mast. e aplicação da morfologia polínica à nova classifi cação infragenérica de Passifl ora.…”
Section: Introductionunclassified